2007
DOI: 10.1002/masy.200751016
|View full text |Cite
|
Sign up to set email alerts
|

Polymethacrylate Networks as Substrates for Cell Culture

Abstract: Summary: methacrylate networks have a long history of applications in medical technology and much is known of their non‐fouling properties. However, in recent times it has become clear that the swollen nature of these materials may provide some advantages if they are used as scaffolds in tissue engineering. In general however these hydrogels are resistant to protein adsorption and human cells do not easily adhere. In this work we provide an overview of several strategies that are designed to improve the cell‐a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Recently, the underlying principles that control these properties are emerging but there is still much to be determined in the detail of how synthetic materials affect cell attachment, proliferation and differentiation. In our recent work, we have shown that control of polymer network architecture and synthesis conditions, which ultimately control bulk and surface morphology, can have profound effects on cell behavior 1–3. We have also shown that the addition of specific alkyl amine groups can convert previously non‐adhesive hydrogel substrates into excellent supports for cell culture 1, 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the underlying principles that control these properties are emerging but there is still much to be determined in the detail of how synthetic materials affect cell attachment, proliferation and differentiation. In our recent work, we have shown that control of polymer network architecture and synthesis conditions, which ultimately control bulk and surface morphology, can have profound effects on cell behavior 1–3. We have also shown that the addition of specific alkyl amine groups can convert previously non‐adhesive hydrogel substrates into excellent supports for cell culture 1, 4.…”
Section: Introductionmentioning
confidence: 99%
“…However, conventional non‐charged hydrogels are essentially non‐adhesive for cells and they are poor substrates for cell culture. In a previous volume in this series of symposia from the Polymer Networks Group, we described how both amphiphilic conetworks and alkyl‐aminated hydrogels were excellent substrates for cell culture 1. In this article we report our most recent work on understanding how to modify hydrogels for cell attachment.…”
mentioning
confidence: 99%
“…1 Hence, these conetworks are generally employed in the synthesis of drugdelivery systems, 4 scaffolds for tissue engineering, 5 biocatalysts and nanoreactors, 6 contact lenses, 7 biosensors 8 and body implants. 9 In particular, application in tissue engineering and drug delivery not only aim at the above mentioned properties, but it is also desirable to change these properties in response to an external stimulus.…”
Section: Introductionmentioning
confidence: 99%
“…Wertheimer and coworkers demonstrated the critical importance of the primary amine (NH 2 ) of nitrogen‐rich plasma‐polymerized ethylene films by correlating selective cell adhesion of human U‐937 macrophages on the surfaces with varying nitrogen concentrations . Sun et al investigated a strategy for promoting cell‐adhesive properties of polymethacrylate hydrogel networks that were composed of 2,3,‐propandiol‐1‐methacrylate (GMMA), dodecyl methacrylate (DM), and ethandiol dimethacrylate (EDMA) modified with various amounts of methacrylic acid (MA) . Human dermal fibroblasts (HDFs) cultured on the hydrogels containing various amounts of MA did not spread well and were poorly attached to all of the hydrogels.…”
Section: Introductionmentioning
confidence: 99%